Synthesis of Phenyl Esters Using SiO2-SO3H Catalyst in Conventional Heating and Microwave-Irradiated Esterification Processes - Barbosa, Sandro L.; Ottone, Myrlene; Freitas, Milton de S.; Lima, Camila D.; Nelson, David L.; Clososki, Giuliano C.; Caires, Franco J.; Klein, Stanlei I. [UNESP]; Hurtado, Gabriela R. [UNESP] (Amer Scientific Publishers, 2019)
A SiO2-SO3H amorphous catalyst containing a small surface area of 115.0 m(2)g(-1) and 1.32 mmol H+/g was prepared from fine construction sand and sodium carbonate and sulfonated with H2SO4. In a 10% (w/w) basis, it is very efficient for catalyzing the esterification of carboxylic acids with phenol. The reaction processes were performed using conventional heating and under microwave irradiation. The yields were higher in the microwave-irradiated esterification. The catalyst could be used for three esterification sequences in both processes.
Keywords: Micro-Meso-Macroporosity Catalyst; Phenyl Esters; Solvent Free Esterification; Microwave Irradiation; Phenyl Acetate; Diphenyl Oxalate; Diphenyl Carbonate Precursor